Group-based food and nutritional education for the treatment of obesity in adult women using the family health strategy - Serenini BERNARDES, Milena; MARÍN-LÉON, Letícia (Revista de Nutrição, 2023)
Objective The high prevalence of obesity and its association with chronic diseases is a major public health problem. This study aimed to evaluate a group-based Food and Nutrition Education Program for the treatment of excess weight in Brazilian women attending the Family Health Strategy. Methods This quasi-experimental intervention study was conducted among 172 women, including 87 women in the intervention group who participated in a nutritional education program that addressed topics in the area of nutrition. The Intervention and Control groups underwent an anthropometric evaluation at the beginning of the study and at the 6th month. Results At the end of the intervention, the intervention group showed a significant reduction in weight and Body Mass Index, while the control group showed an increase in these variables. Women who completed the intervention (n=71) showed a mean difference of -5.15 kg and a reduction of 2.04 points in the Body Mass Index. Still 50.7% of the participants in the intervention group achieved a weight loss greater than or equal to 5.0%, and 40.8% of them maintained this reduced weight for up to seven months after the end of the intervention. Conclusion This study emphasizes the importance of group-based food and nutritional education interventions to promote and maintain weight loss, and thus, prevent and treat chronic diseases.